2023
DOI: 10.1590/1980-5373-mr-2022-0613
|View full text |Cite
|
Sign up to set email alerts
|

Study of Surface Modification of Niobium Caused by Nitriding and Cathodic Cage Deposition

Abstract: In this work, plasma nitriding (PN) and cathode cage plasma deposition (CCPN) treatments were carried out with temperatures of 400 and 450 °C to evaluate the modifications caused on the surface of pure niobium samples. XRD, SEM, Vickers microhardness, and sphere-disk analyses were used to characterize the coatings' composition, morphology, hardness, and wear resistance. The results showed that the treated samples increased hardness and wear resistance, with the sample submitted to CCPN at 450 °C presenting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The literature reports the use of different alloys (silver 29 , copper 30 , titanium 31 , nickel 32 , chromium 33 , nickel/chromium 34 ) in the composition of the cage for the treatment of metallic samples 26 . Macedo et al 35 , increased samples' hardness and wear resistance with niobium cathodic cage plasma treatment. Silva et al 26 , demonstrated that CCPD on stainless steel exhibited good performance in terms of corrosion resistance at low temperatures (350°C).…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports the use of different alloys (silver 29 , copper 30 , titanium 31 , nickel 32 , chromium 33 , nickel/chromium 34 ) in the composition of the cage for the treatment of metallic samples 26 . Macedo et al 35 , increased samples' hardness and wear resistance with niobium cathodic cage plasma treatment. Silva et al 26 , demonstrated that CCPD on stainless steel exhibited good performance in terms of corrosion resistance at low temperatures (350°C).…”
Section: Introductionmentioning
confidence: 99%